Research on end hopping for active network confrontation - SHI Le-yi1; 2; JIA Chun-fu2 (Tongxin xuebao)
Motivated by frequency hopping for military communication, end hopping tactic was proposed which can mitigate those threats such as DoS and eavesdrop greatly by changing the end information of port, address, timeslot, cryptographic algorithm or even protocol pseudo-randomly during end to end transmission. An active defense model has been established upon end hopping. Then a test-bed has been implemented through mobile agent with a successful solu- tion of synchronization and handoff. The model shows better performance in both theoretical analysis and empirical studies. The work demonstrates that end information hopping tactic is feasible and effective for active network confronta- tion.